The impact of a metacognition-based course on school students’ metacognitive skills and biology comprehension - Sadykova, Ainur; Iskakova, Marzhan; Ismailova, Gulnara; Ishmukhametova, Albina; Sovetova, Anar; Mukasheva, Kuralay (Frontiers in Education, 2024)
The fast-paced and intricate nature of the current society, coupled with the ongoing changes in educational requirements, calls for the cultivation of higher-order thinking skills. To that end, adopting metacognitive strategies could be instrumental. This paper aimed to evaluate the effects of a 10-week-long metacognition-based biology course on school students' metacognition and biology comprehension.Methods: Employing a mixed-methods quasi-experimental design, the study involved 120 eighthgraders from two public schools. One group was exposed to metacognitive questioning, while the other one continued with regular classroom activities.The results showed that participants who received metacognition-guided instruction achieved higher scores on the biology test and reported improved metacognition as compared to those who followed the standard curriculum. These outcomes were consistent across genders and regardless of whether a student reported a deep or surface learning approach. Qualitative analysis extracted themes of collaboration and understanding among the students. They appreciated the specificity of tasks, which deepened their comprehension, and valued collaborative learning facilitated by metacognitive prompts. These prompts not only enhanced their understanding but also contributed to fostering a positive classroom environment.This research underscores the effectiveness of metacognitive support in enhancing biology education. It advocates for the integration of metacognitive strategies into classroom practices, emphasizing the positive impact they can have on students' learning experiences and outcomes.